PHACOVITRECTOMY FOR PRIMARY RHEGMATOGENOUS RETINAL DETACHMENT REPAIR: A Retrospective Review. Issue 4 (April 2021) - Benson, Matthew D.; Sia, David; Seamone, Mark E.; Greve, Mark; Hinz, Brad; Tennant, Matthew T. S.; Baker, Chad; Somani, Rizwan; Ehmann, David S.
Abstract : Purpose: To analyze the single surgery success rate and anterior segment complications related to phacoemulsification and intraocular lens implantation in a series of patients undergoing phacovitrectomy for all types of primary rhegmatogenous retinal detachment. Methods: We performed a retrospective interventional case series on 302 eyes undergoing phacovitrectomy for primary rhegmatogenous retinal detachment repair between November 1, 2016, and February 2, 2019, in Edmonton, Canada. Primary outcomes included single surgery retinal reattachment rate and anterior segment complications. Secondary outcomes included the effects of proliferative vitreoretinopathy and macula and/or peripheral internal limiting membrane peeling on the rate of surgical success. Results: The single surgery success rate of phacovitrectomy for all types of primary rhegmatogenous retinal detachment was 85.1%. The presence of proliferative vitreoretinopathy was associated with lower surgical success (odds ratio, 0.33; P = 0.01). Macular internal limiting membrane peeling was associated with higher surgical success (odds ratio, 2.4; P = 0.05). Anterior segment complications included posterior capsular opacification (28.8%), posterior synechiae (10.9%), and posterior capsular rupture (2.3%). Conclusion: Phacovitrectomy is a safe and effective treatment option for the primary repair of rhegmatogenous retinal detachments. This study provides evidence to support the safe incorporation of phacoemulsification and intraocular lens implantation with retinal surgery. Abstract : A retrospective case series of 302 patients who underwent phacovitrectomy for all types of rhegmatogenous retinal detachment was performed. The single surgery success rate was 85.1%. We present all associated anterior segment complication rates and conclude that phacovitrectomy for primary rhegmatogenous retinal detachment repair is safe and effective.